Nonrenewable Resources : A Case for Persistent Fiscal Surpluses - Alier, Max (IMF Working Papers; Working Paper ;, 1999)
This paper examines whether there is a case for temporary but persistent fiscal surpluses in economies heavily endowed with nonrenewable resources. It finds that there generally is a case. Fiscal surpluses permit replacing nonfinancial wealth with financial assets, the return on which increases public consumption possibilities of future generations for a constant across-generation tax burden. The more biased are a government's preferences toward present generations, the lower will be the initial surpluses; the larger the finite endowment, the larger the initial surpluses. In a more general framework, including public investment, the proposition could be rephrased by replacing surpluses with stronger initial fiscal positions.